2018
DOI: 10.1177/0046958018755483
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Total Inpatient Pharmacy Cost at a Tertiary Hospital in Malaysia: A Retrospective Study

Abstract: The steady growth of pharmaceutical expenditures is a major concern for health policy makers and health care managers in Malaysia. Our study examined the factors affecting the total inpatient pharmacy cost (TINPC) at the Universiti Kebangsaan Malaysia Medical Centre (UKMMC). In this retrospective study, we used 2011 administration electronic prescriptions records and casemix databases at UKMMC to examine the impact of sociodemographic, diagnostic, and drug variables on the TINPC. Bivariate and multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In the MYDRG system, patients are classified into 3 severity levels: severity level I (no complications or comorbidities), severity level II (minor complications or comorbidities), and severity level III (major complications or comorbidities). 13 Following the algorithm, the grouper software determines the severity level based on the secondary diagnoses and procedures using ICD10 and ICD 9-CM. Patients with incomplete information, those with unavailable charts because they were admitted to private wards, and nongroupable cases were excluded from the study.…”
Section: Study Population and Data Extractionmentioning
confidence: 99%
“…In the MYDRG system, patients are classified into 3 severity levels: severity level I (no complications or comorbidities), severity level II (minor complications or comorbidities), and severity level III (major complications or comorbidities). 13 Following the algorithm, the grouper software determines the severity level based on the secondary diagnoses and procedures using ICD10 and ICD 9-CM. Patients with incomplete information, those with unavailable charts because they were admitted to private wards, and nongroupable cases were excluded from the study.…”
Section: Study Population and Data Extractionmentioning
confidence: 99%
“…Chaikledkaew et al (2008) suggested that patient age and sex are determinants of health-care costs and hospitalisation probability. Ariwardani et al (2019) discovered that patient age is one of the causes of differences in DRG rates and hospital costs in Indonesia, while Aljunid and Jadoo (2018) found that total inpatient pharmacy costs in a Malaysian University Hospital were determined by patient gender. More recently, Xu et al (2020) discovered that age has a positive association with hospitalization cost of patients in Chinese Naval hospitals.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Compared to other industries, where big data has been used intensively and optimally for forecasting costs, a limited application of BDA in hospitals has been noted (Qing and Liu, 2019). Prior studies have defined determinants of patient costs and their variation with DRG rates using machine learning tools (for instance, Aljunid and Jadoo, 2018;Nelson-Williams et al, 2016;Wu et al, 2020;Kuo et al, 2018).Testing mathematical models to predict cost recovery of DRG, this study also explores the potential roles of BDA in the acceleration of MACs in the hospital.…”
Section: Introductionmentioning
confidence: 99%
“…The average cost for a patient treated from Coronavirus in a range of five to ten days is approximately (IQD 573,228) (equivalent to USD 477.69, exchange rate 1 US Dollar (USD)= Iraqi Dinar (IQD)1200 in November 2020 ). The cost is directly proportional to the period of treatment and the emergence of complications [11].…”
Section: Estimated Cost To Treat Covid-19 Patients At Private Clinicsmentioning
confidence: 99%
“…The need to reform the Iraqi health system has become an urgent necessity through the implementation of effective health economic policies, such as the adoption of universal health insurance (UHI). Moreover, technical, and clinical systems such as the Diagnosis Related Group (DRG) or Case-mix are preferable systems that precisely detect the allocated cost per service and patient cost estimation [11,12].…”
Section: Estimated Cost To Treat Covid-19 Patients At Private Clinicsmentioning
confidence: 99%